All Days 2013
DOI: 10.2523/iptc-16742-ms
|View full text |Cite
|
Sign up to set email alerts
|

First Steps of Channel Fracturing in Russia Set New Directions for Production Increase of the Oil Fields

Abstract: Channel fracturing technique changes the concept of proppant fracture conductivity generation by enabling hydrocarbons to flow through open channels instead of the proppant pack. The new technique is based on four main components: proppant pulsing at surface with fracturing equipment and software, a special perforation strategy, fibrous material to deliver stable channels, and a set of models to optimize channels geometry. Channel fracturing in Russia's oil fields began in 2008 as field testing operations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Sadykov et al (2012) have demonstrated that channel fracturing can be a valuable option for production enhancement with refracturing treatments with reduced risk of screenout. It was previously demonstrated that the effect of adding a fiber material to crosslinked fluid is the reduction of total friction pressure by an average of 17 to 29% depending on proppant concentration (Yudin et al 2013). The fiber-laden fluid described in this paper used similar fibrous material under the same concentrations as channel fracturing.…”
Section: Benefitsmentioning
confidence: 96%
“…Sadykov et al (2012) have demonstrated that channel fracturing can be a valuable option for production enhancement with refracturing treatments with reduced risk of screenout. It was previously demonstrated that the effect of adding a fiber material to crosslinked fluid is the reduction of total friction pressure by an average of 17 to 29% depending on proppant concentration (Yudin et al 2013). The fiber-laden fluid described in this paper used similar fibrous material under the same concentrations as channel fracturing.…”
Section: Benefitsmentioning
confidence: 96%